TIME OF ACCESS OF GREEN MASS TRITICALE IN WINTER - Войцеховская, Елена; рак, Александр; Худолей, Лариса; Свистунова, Ирина; Ребезов, Максим; Полторецький, Сергей (SWorldJournal, 2020)
This article considers the influence of sowing dates and biological features of the variety rates of phenological development of triticale plants. It was found that among the studied varieties, the earing phase occurs earlier in varieties AD 3/5, AD 44 an